Preparation of New Biofilms Suitable for Manufacturing Processes for A sustainable Environment - Noor A. Oudah; Rahab A. Al-Madany; Zena A. Mahdi; Suhad A. Hussain; Farqad A. Albaidhani; Eussur N. Alkhafaji; Rasha Alali (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2025)
Biodegradable biofilms are sustainable environmental solution and are increasingly important with the increasing awareness of consumers about the environment. This study aimed to prepare and characterize biodegradable poly-3-hydroxybutyrate (P3HB) films with improved physical and chemical properties after incorporation with plant extracts. These biofilms are antibacterial for use in food packaging and medical supplies. The new (P3HB) bioplastic films were prepared using casting technique. The prepared biofilms were the first P3HB/G (resulting from P3HB and ginger extract) and the second P3HB/C (resulting from P3HB and clove extract). All the mentioned biofilms were compared to the P3HB/M which was prepared from P3HB and chloroform only. The thickness, moisture, dissolvability and swelling of the new resulted biofilms were measured. Their chemical and morphological properties were studied using SEM and FTIR. Their ability to inhibit Staphylococcus aureus and Escherichia coli were evaluated, as well as their efficiency in food packaging and preservation. The obtained results demonstrated that the P3HB/C and P3HB/G films exhibit good chemical, physical and antibacterial properties due to the phytochemicals incorporated into the polyester polymer or loaded into their matrix. Thickness, moisture and swelling for P3HB/C and P3HB/G were significantly different; compared to P3HB/M. Yet, when comparing P3HB/C and P3HB/G, the moisture was the only markedly various. The prepared biodegradable packaging materials are great alternatives to conventional plastics since it could be friendly ones to environment